2010
DOI: 10.4049/jimmunol.1000358
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of IL-1β Production and Inflammatory Response by the Mouse Irm1 Locus

Abstract: Material Supplementary 8.DC1http://www.jimmunol.org/content/suppl/2010/07/06/jimmunol.100035

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 19 publications
1
42
0
5
Order By: Relevance
“…3 Using genotype data of 1064 autosomal single nucleotide polymorphisms (SNPs) in 281 (AIRmax  AIRmin) F2 mice, we analyzed genetic clustering and computed the gap statistics, allowing up to 100 null simulations. Visual inspection of the hierarchical plot suggested that the F2 population clusters into several genetically related subgroups (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Using genotype data of 1064 autosomal single nucleotide polymorphisms (SNPs) in 281 (AIRmax  AIRmin) F2 mice, we analyzed genetic clustering and computed the gap statistics, allowing up to 100 null simulations. Visual inspection of the hierarchical plot suggested that the F2 population clusters into several genetically related subgroups (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…This locus was not detected in a previous genetic linkage analysis of pedigrees in the same F2 mice. 3 On chromosome 7, the Irm1 locus was confirmed as linked to both infiltrating cell number and IL-1b production. In particular, for cell number phenotype, the rs13479477 SNP (P ¼ 6.3 Â 10…”
Section: à5mentioning
confidence: 99%
See 3 more Smart Citations